Dimethylarginine dimethylaminohydrolase 1 as a novel regulator of oligodendrocyte differentiation in the central nervous system remyelination. Issue 11 (16th July 2021) - Uyeda, Akiko; Quan, Lili; Kato, Yuki; Muramatsu, Nagaaki; Tanabe, Shogo; Sakai, Kazuhisa; Ichinohe, Noritaka; Kawahara, Yukio; Suzuki, Tatsunori; Muramatsu, Rieko
Abstract: Remyelination is a regenerative process that restores the lost neurological function and partially depends on oligodendrocyte differentiation. Differentiation of oligodendrocytes spontaneously occurs after demyelination, depending on the cell intrinsic mechanisms. By combining a loss‐of‐function genomic screen with a web‐resource‐based candidate gene identification approach, we identified that dimethylarginine dimethylaminohydrolase 1 (DDAH1) is a novel regulator of oligodendrocyte differentiation. Silencing DDAH1 in oligodendrocytes prevented the expression of myelin basic protein in mouse oligodendrocyte culture with the change in expression of genes annotated with oligodendrocyte development. DDAH1 inhibition attenuated spontaneous remyelination in a cuprizone‐induced demyelinated mouse model. Conversely, increased DDAH1 expression enhanced remyelination capacity in experimental autoimmune encephalomyelitis. These results provide a novel therapeutic option for demyelinating diseases by modulating DDAH1 activity. Main Points: Loss of functional screening identified DDHA1 as a novel regulator of oligodendrocyte differentiation. An inducer of DDHA1 expression enhanced the remyelination capacity in EAE.